EPD1504: a novel μ-opioid receptor partial agonist attenuates obsessive–compulsive disorder (OCD)-like behaviors - Youngblood, Beth; Medina, Julio C.; Gehlert, Donald R.; Schwartz, Neil (Frontiers in Psychiatry, 2023)
Low doses of mu opioid receptor (MOR) agonists rapidly ameliorate symptoms in treatment resistant obsessive-compulsive disorder (OCD) patients (10-50% of OCD patients). However, the utility of MOR agonists is limited by their safety liabilities. We developed a novel MOR partial agonist (EPD1540) that has an improved respiratory safety profile when compared to buprenorphine; buprenorphine is a MOR partial agonist primarily used in the treatment of opiate use disorder that in investigator lead trials has been shown to rapidly ameliorate symptoms in treatment resistant OCD patients. Here we show that doses of EPD1504 and buprenorphine that occupy small fractions of MORs in the CNS (approximately 20%) are as effective as fluoxetine at ameliorating OCD-like behaviors in two different rat models (an operant probabilistic reversal task and marble burying). Importantly, effective doses of EPD1504 did not impair either locomotor activity (in the open field test or lever pressing in the operant behavior), or respiration under normoxic or hypercapnic conditions. Additionally, EPD1504 had effects comparable to buprenorphine in the conditioned place preference assay. Together these results indicate that EPD1504 may provide a safer alternative to buprenorphine for the treatment of OCD patients